2018
DOI: 10.1177/0300985818759770
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Labeling of Multiple Myeloma Oncogene 1/Interferon Regulatory Factor 4 (MUM1/IRF-4) in Canine Cutaneous Histiocytoma

Abstract: Multiple myeloma oncogene 1/interferon regulatory factor 4 (MUM1/IRF-4) immunohistochemistry (IHC) is mainly used for diagnostic confirmation of plasma cell tumors (PCTs) in dogs and cats. This article describes MUM1/IRF-4 IHC expression in 20 cases of canine cutaneous histiocytoma (CH) and compares it with 10 cutaneous or mucocutaneous PCTs and 5 cutaneous histiocytic sarcomas (HSs) submitted to the same IHC protocol. All histiocytomas had strong nuclear and variable cytoplasmic immunolabeling for MUM1/IRF-4,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 14 publications
(42 reference statements)
1
25
0
2
Order By: Relevance
“…4,25 In our study, a high percentage (96%) of PCTs were MUM1 positive, in agreement with previous reports (93.5-100%). 24,30 Given this high sensitivity, IHC for MUM1 is routinely used to confirm the plasma cell origin in canine tumors, often replacing the IHC for light chains. 12,24 However, the specificity of MUM1 for PCTs has recently been questioned by a study that demonstrated consistent expression of MUM1 in a series of 20 canine histiocytomas.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…4,25 In our study, a high percentage (96%) of PCTs were MUM1 positive, in agreement with previous reports (93.5-100%). 24,30 Given this high sensitivity, IHC for MUM1 is routinely used to confirm the plasma cell origin in canine tumors, often replacing the IHC for light chains. 12,24 However, the specificity of MUM1 for PCTs has recently been questioned by a study that demonstrated consistent expression of MUM1 in a series of 20 canine histiocytomas.…”
Section: Discussionmentioning
confidence: 99%
“…36 For this reason, distinguishing poorly differentiated PCTs from other round cell tumors may represent a diagnostic challenge. 30 Immunohistochemistry (IHC) for multiple myeloma oncogene 1 (MUM1) is widely used to confirm the diagnosis of PCTs in dogs. 24,30 MUM1 is a transcription factor involved in regulation of cell growth, especially B-cell differentiation.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations